CORROSION TESTS AT THE WATER TREATMENT PLANT IN JAKUBANY - Galík, Matúš; Kriš, Jozef; Ilavský, Ján (GeoScience Engineering, 2014)
External corrosion, which depends on environmental and operating conditions, is the main cause of structural deterioration of all metallic mains. Internal corrosion, on the other hand, can cause significant functional (hydraulic, water quality) deterioration within a distribution system. This work deals with the corrosion of water pipes which greatly affects the durability and failure rate of water systems. The test is evaluated in accordance with STN 75 7151 and ASTM D2688-11. The corrosion tests were carried out on raw and treated water at the water treatment plant in Jakubany.